2015
DOI: 10.1007/s11250-015-0771-1
|View full text |Cite
|
Sign up to set email alerts
|

Vector identification and clinical, hematological, biochemical, and parasitological characteristics of camel (Camelus dromedarius) theileriosis in Egypt

Abstract: The objectives of the present study were to identify a possible tick vector and to determine the prevalence of camel theileriosis in Egypt using blood smears stained with Giemsa's stain and PCR assay. Hemogram and serum biochemical constituents were also investigated. A total of 243 camels, aged 3-5 years, were examined. The results revealed that 75 (30.86 %) camels were infected with Theileria spp. of Giemsa-stained blood smears. Hyalomma dromedarii was identified as the carrier tick of Theileria spp. Multinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 23 publications
2
30
1
1
Order By: Relevance
“…By using PCR assay, 71.9% of investigated camels were having theileriosis caused by Theileria sp. and the incidence of infection was 71.4% in females and 73.3% in males in agreement with those previously reported [44][45][46][47]. Higher and lower rates of Theileria camelensis ranged from 6.9% to 75% were recorded in Egypt by different authors [43,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…By using PCR assay, 71.9% of investigated camels were having theileriosis caused by Theileria sp. and the incidence of infection was 71.4% in females and 73.3% in males in agreement with those previously reported [44][45][46][47]. Higher and lower rates of Theileria camelensis ranged from 6.9% to 75% were recorded in Egypt by different authors [43,[46][47][48][49].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, T. annulata infections were found in 3 Hy. asiaticum ticks collected from camel, consistent with studies that reported T. annulata infection in Hyalomma tick parasitizing camels and T. annulata being the most abundant piroplasm in camels (El Kammah et al, 2001;Youssef et al, 2015). Our finding further confirms the evidence of low host specificity of T. annulata.…”
Section: Discussionsupporting
confidence: 92%
“…As detailed in Table , H. dromedarii was described for the first time in 1990s as a ‘new’ natural vector of T. annulata in Mauritania (Jacquiet, Colas, Cheikh, Thiam, & Ly, ; Jacquiet et al., ). Subsequently, a report from Egypt implicated this tick in the transmission of T. annulata on the basis of molecular detection in camels and microscopic observation of the parasite in the tick salivary glands (Youssef et al., ). In addition, in Sudan H. dromedarii has also been implicated as possible vector of T. annulata on the basis of epidemiological observations (Ahmed in Guma et al, ; Mohammed et al., ) and experimental findings (Mustafa et al., ).…”
Section: Agro‐ecological Zones and Transmission Patternsmentioning
confidence: 99%